Development and characterization of folate anchored Saquinavir entrapped PLGA nanoparticles for anti-tumor activity. (2nd November 2015) - Singh, Ruchi; Kesharwani, Prashant; Mehra, Neelesh Kumar; Singh, Shashank; Banerjee, Smita; Jain, N. K.
Abstract: Objective : Saquinavir (SQV) is a US-FDA approved HIV protease inhibitor (HPI) for HIV cure. The purpose of the present investigation was to develop and characterize the anticancer potential of the SQV-loaded folic acid (FA) conjugated PEGylated and non-PEGylated poly(d, l -lactide-co-glycolide) (PLGA) nanoparticles (NPs) (SQV–Fol–PEG–PLGA and SQV–Fol–PLGA) employing PC-3 (human prostate) and MCF-7 (human breast) cancer cell lines. Materials and methods : Developed NPs were characterized by IR, NMR, DSC, XRD, size, charge and further tested for drug loading and cellular uptake properties. Result : The entrapment efficiency was found to be 56 ± 0.60 and 58 ± 0.80 w/v for SQV–Fol–PEG–PLGA and SQV–PLGA NPs, respectively. The obtained results of SQV–Fol–PEG–PLGA showed enhanced cytotoxicity and cellular uptake and were most preferentially taken up by the cancerous cells via folate receptor-mediated endocytosis (RME) mechanism. At 260 µM concentration, SQV–PLGA NPs and SQV–Fol–PEG–PLGA NPs showed 20%, 20% and 23% cell growth inhibition in PC-3 cells, respectively whereas in MCF-7 cells it was 12%, 15% and 14% cell growth inhibition, respectively. Conclusions : Developed targeted SQV–Fol–PEG–PLGA NPs were superior anticancer potential as compared to non-targeted SQV–PLGA NPs. Thus, these targeted NPs provide another option for anticancer drug delivery scientists.